Shakespeare and the truth-teller : confronting the cynic ideal - Hershinow, David (Edinburgh University Press, 2019)
Highlighting the necessity of literary thinking to political philosophy, this book explores Shakespeare's responses to sixteenth-century debates over the revolutionary potential of Cynic critical activity.
Keywords: Shakespeare, William, -- 1564-1616 -- Philosophy.; Shakespeare, William, -- 1564-1616 -- Criticism and interpretation.; Shakespeare, William, -- 1564-1616; Cynicism in literature.; Realism in literature.; Cynisme dans la littérature.; Réalisme dans la littérature.; LITERARY CRITICISM -- Shakespeare.; Philosophy; Cynicism in literature; Realism in literature; Criticism, interpretation, etc.